Meaning of The Word Ta'lamun in The Qur'an - Hidayah, Nurul; Rasyid, Ahmad Ridwan Al; Windarto, Cahyani (QiST: Journal of Quran and Tafseer Studies, 2024)
The development of meaning occurs in all words in the world. This happens because humans interact with words from a language so that over time they will develop. These changes can be in the form of specializing a word, expanding a word, increasing the meaning of a word, decreasing the quality of a word, deleting the meaning of a word, or multiplying a meaning. This research focuses on library research by examining the word ta'lamun which is used in the verses of the Qur'an. From the verses of the Qur'an studied, it was found that the word ta'lamun experienced a development in the meaning of the word in terms of specialization of meaning, so that the meaning of ta'lamun has a meaning that adapts to the context of the sentence in which the word ta'lamun is located.